DETERMINAN FAKTOR KEPUASAN KERJA PERAWAT DI RUMAH SAKIT BHAYANGKARA TEBING TINGGI KOTA TEBING TINGGI TAHUN 2020 - Wayati, Endang Tri (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
One element that really determines the quality of hospital health services is health workers. Of the health workers in the Hospital who mainly have a large role are nurses, this is due to the nurse profession having a relatively large proportion that is almost more than 50% of all hospital human resources. The quality of nursing services is strongly influenced by the processes, roles and functions of nursing service management, because nursing management is a special task that must be carried out by the nursing manager / manager which includes planning, organizing, directing and monitoring. This study aims to analyze the determinants of nurse job satisfaction. This is a cross-sectional study conducted at Bhayangkara Tebing Tinggi Hospital Tebing Tinggi City in January to June 2020. Respondents numbered 100 people determined by the minimum sample formula. There is no relationship between age, education level, length of service, marital status, incentives, competence, managerial supervision and hospital facilities with nurse satisfaction at Bhayangkara Tebing Tinggi Hospital in Tebing Tinggi in 2020 based on the results of Multivariate analysis. The most dominant variable affecting Nurse Satisfaction at Bhayangkara Tebing Tinggi Hospital Tebing Tinggi City in 2020 was based on the results of multivariate analysis namely Workload (sig.0.006) and incentives (sig.0.009). It is hoped that it can increase Nurses' Incentives in accordance with UMR / UMD, complete Hospital Facilities especially Hospital lift facilities, conduct training or education programs to improve nurse competencies that researchers assume are variables that cause an increase in workload.